1998
DOI: 10.1073/pnas.95.13.7532
|View full text |Cite
|
Sign up to set email alerts
|

Su(UR)ES: A gene suppressing DNA underreplication in intercalary and pericentric heterochromatin ofDrosophila melanogasterpolytene chromosomes

Abstract: A genetic locus suppressing DNA underreplication in intercalary heterochromatin (IH) and pericentric heterochromatin (PH) of the polytene chromosomes of Drosophila melanogaster salivary glands, has been described. Found in the In(1)sc V2 strain, the mutation, designated as Su(UR)ES, was located on chromosome 3L at position 34.8 and cytologically mapped to region 68A3-B4. A cytological phenotype was observed in the salivary gland chromosomes of larvae homozygous and hemizygous for Su(UR)ES: (i) in the IH region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
197
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(201 citation statements)
references
References 24 publications
3
197
0
1
Order By: Relevance
“…Ultimately this results in complete polytenization of these regions in polytene chromosomes. 13 Second, the decrease in H3K27me3 histones observed in SuUR mutants 11 is, in fact, a result of gradual dilution of H3K27me3 mark in repressed chromatin regions (Fig. 2B).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Ultimately this results in complete polytenization of these regions in polytene chromosomes. 13 Second, the decrease in H3K27me3 histones observed in SuUR mutants 11 is, in fact, a result of gradual dilution of H3K27me3 mark in repressed chromatin regions (Fig. 2B).…”
mentioning
confidence: 99%
“…15 In other aspects SuUR mutants are viable, fertile and show no overt changes in gene expression and Origin Recognition Complex (ORC) binding. 11,13 It is worth mentioning that SuUR is a fast-evolving gene that was found only in Diptera. 16 Despite the low evolutionary conservation, recent studies revealed several important features of Figure 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12 Consequently, these regions undergo full polytenization, as confirmed by direct DNA copy number measurements. 13,14 The SuUR gene encodes for a 962 aa long protein. The N-terminus of the protein (aa 1-250) is moderately homologous to the N-terminal part of an ATPase/helicase domain found in a SNF2/SWI2 family of proteins comprising many well-known chromatin remodelers.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%